Identification And Dosage of Caffeine by Liquid Chromatography UV-Visible in Energy Drinks Marketed in Benin Republic.] - ASSANHOU, Assogba Gabin (My University, 2022)
The consumption of energy drinks is experiencing a sharp increase in the world as in Benin with a flourishing market. Many questions remain as to their composition and their potential health effects. Although their composition varies depending on the brand. The substances most encountered in these drinks are caffeine, taurine, group B vitamins, sugars, and derivatives. Several cases of caffeine intoxication have been reported by US poison control centers following the consumption of these energy drinks. These facts, despite their seriousness, however, remain poorly documented. We have undertaken through the present study, the identification, and the assay by liquid chromatography UV-visible of caffeine in 34 samples of energy drinks collected in 15 supermarkets of Cotonou in Benin Republic after some preliminary tests of visual inspection, measurements of the beverage volume and pH. From the physicochemical analysis of the drinks, it appears that all the samples (n = 34) contained caffeine at levels varying from 12.7mg/ 100mL to 51.3mg/ 100mL (NAFDAC standard: 14.5 to 32mg / 100mL). The non-conformities noted were under assay (1/34 samples; 12.7±0.2mg/100mL); overdose (1/34 samples; 51.3±1.1 mg/100mL)); risk of overdose (7/34 samples). All samples passed the tests for volume (251.7 < <506.7mL) and pH (2.7 pH <3.8; Standard: 2.7 pH <4.0) while 20/34 samples did not pass the visual inspection test. It is urgent that the public authorities in charge of food security ensure the control to protect the health of the populations.
Keywords: Quality Control; Energy Drinks; Caffeine; Identification; Dosage